Update on Pseudotumor Cerebri (Idiopathic Intracranial Hypertension) - Hoffmann, Jan; May, Arne (Neurology International Open, 2017)
Idiopathic intracranial hypertension is characterized by an increase of intracranial pressure of unknown etiology. The clinical presentation is dominated by progressive visual disturbances, which are commonly the result of a papilledema, headache and cranial nerve palsies. Clinical studies have revealed over the past years that the syndrome may also be associated with olfactory disturbances, cognitive deficits and a pulsatile tinnitus.The underlying pathomechanism is probably based on a disturbance of venous outflow, which causes a reduced absorption of cerebrospinal fluid that results in an increase of cerebrospinal fluid pressure. It remains unclear if the venous outflow disturbance results from the overweight-induced increase of intrathoracic pressure, the presence of sinus vein stenoses or both conditions. Recently hormonal factors have also been discussed, but the mechanisms behind a potential influence on intracranial pressure remain unclear.Treatment of idiopathic intracranial hypertension relies mainly on an effective body weight reduction and medication with carboanhydrase inhibitors, which can reduce the production of cerebrospinal fluid and body weight. Results of the first randomized, placebo-controlled trial as well as a 12-month follow-up show that acetazolamide effectively reduces papilledema, visual disturbances and headache in idiopathic intracranial hypertension. In contrast, the evidence for the carboanhydrase inhibitors topiramate and furosemide still relies on open-label trials, because double-blind, placebo-controlled trials for their efficacy in idiopathic intracranial hypertension do not exist. In addition to the treatment with carboanhydrase inhibitors, increasing evidence suggests that the somatostatin analog octreotide may be effective in the treatment of idiopathic intracranial hypertension, but to date no randomized, double-blind, placebo-controlled trials exist to confirm this observation.
Keywords: pseudotumor cerebri; idiopathic intracranial hypertension; headache